The influence of modality on input, visuo-motor coordination, and execution in the advanced pianist's sight-reading processes - Qi, Jing; Adachi, Mayumi (Frontiers in Psychology, 2022)
In this study, we explored how the modality (major and minor) would affect the input (i.e., fixation), visuo-motor coordination (i.e., eye-hand span and time of performance), and execution (i.e., errors) in the advanced pianist’s sight-reading processes, as well as relations among these three phases. Thirty-two advanced pianists with 5-54 years of piano training participated in the study. All participants sight-read three two-voice pieces in either major (n = 16) or minor (n = 16) mode while their eye movements were measured by an eye-tracking device (30 fps). All pieces were 20-measure long written in 4/4 meter, adapted from unfamiliar Baroque pieces. Results showed that sight-readers fixated more frequently and tended to spend more time performing in a minor score than in a major score. This implies that modality of a score affects an efficiency of input and visuo-motor coordination in the advanced pianist’s sight-reading. Spearman’s correlation coefficients showed that errors were correlated positively with the number of fixations and the duration of performance. These results add more evidence to the notion that efficiencies in input and visuo-motor coordination are related to the accuracy in execution.